Strategic pricing, market entry and competition: Evidence from German electricity submarkets - Vigen Nikogosian; Tobias Veith (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
In German electricity submarkets for residential customers standard contracts offered by former monopolists are the more costly option for customers who have not switched to an alternative contract yet. As most German households are served with this contract type we follow the Limit Pricing theory and show that standard contract price could be used as an instrument to affect competition, in terms of market entries, in the related market. We theoretically derive the optimal price-setting behavior of a price-discriminating incumbent provider and show that under particular circumstances reducing the standard contract price could increases the incumbent's profit. We then analyze our theoretical findings employing data for German retail electricity submarkets using simultaneous equation approach and can find support for our hypothesis. In particular for customers with low consumption and high relative switching costs the results show that the standard contract price can affect market entry whereas for high consumption level customers we have to reject our hypothesis.
Keywords: L11; L13; L43; L94; 330; barrier to entry; first-mover advantage; price discrimination; Elektrizitätswirtschaft; Markteintritt; Preisdifferenzierung; Vertrag; Wohnimmobilien; Theorie; Deutschland